Comparison of hysterosalpingography diagnostic value with laparoscopy and hysteroscopy findings in infertility research (Annals of Medical Research, 2023)
Aim: To compare hysterosalpingography (HSG) findings with laparoscopy (LS) and hysteroscopy (HS) findings in infertile patients and evaluate their adequacy in diagnosisMaterials and Methods: The presented retrospective study was conducted on 106 patients diagnosed with primary and secondary infertility. LS-HS procedure was applied to the cases who could not get pregnant at the end of six months after HSG. Sociodemographic data and tubal, uterine, endometrial, and pelvic findings were compared. Sensitivity, specificity, and positive and negative predictive values were calculated.Results: Primary infertility was observed at a higher rate. (n=68, 64.2%). Most of the patients were in the 24-29 age group. The maximum duration of infertility has been observed in the range of 1-4 years. Compared with LS in tubal patency, the sensitivity of HSG was 85%, specificity 65%, positive predictivity 88.3%, and negative predictivity 58.6%. Compared with HS in detecting uterine pathologies, the sensitivity of HSG was 94.9%, specificity 53.3%, positive predictivity 72.7%, and negative predictivity 89.7%.Conclusion: In evaluating infertile patients, HSG is reliable in detecting tubal blockade. Due to its low specificity, invasive methods can be applied, especially in unexplained infertility whose pathology is not seen in HSG. These methods are complementary rather than the alternative.
Keywords: Female infertility; Hysterosalpingography; Laparoscopy; Hysteroscopy